Plastid phylogenomics reveals evolutionary relationships in the mycoheterotrophic orchid genus Dipodium and provides insights into plastid gene degeneration - Goedderz, Stephanie; Clements, Mark A.; Bent, Stephen J.; Nicholls, James A.; Patel, Vidushi S.; Crayn, Darren M.; Schlüter, Philipp M.; Nargar, Katharina (Frontiers in Plant Science, 2024)
The orchid genus Dipodium R.Br. (Epidendroideae) comprises leafy autotrophic and leafless mycoheterotrophic species, the latter confined to sect. Dipodium. This study examined plastome degeneration in Dipodium in a phylogenomic and temporal context. Whole plastomes were reconstructed and annotated for 24 Dipodium samples representing 14 species and two putatively new species, encompassing over 80% of species diversity in sect. Dipodium.Orchidaceae found sect. Leopardanthus as sister lineage to sect. Dipodium. Dipodium ensifolium, the only leafy autotrophic species in sect. Dipodium was found sister to all leafless, mycoheterotrophic species, supporting a single evolutionary origin of mycoheterotrophy in the genus. Divergence time estimations found that Dipodium arose ca. 33.3 Ma near the lower boundary of the Oligocene and crown diversification commenced in the late Miocene, ca. 11.3 Ma. Mycoheterotrophy in the genus was estimated to have evolved in the late Miocene, ca. 7.3 Ma, in sect. Dipodium. The comparative assessment of plastome structure and gene degradation in Dipodium revealed that plastid ndh genes were pseudogenised or physically lost in all Dipodium species, including in leafy autotrophic species of both Dipodium sections. Levels of plastid ndh gene degradation were found to vary among species as well as within species, providing evidence of relaxed selection for retention of the NADH dehydrogenase complex within the genus. Dipodium exhibits an early stage of plastid genome degradation as all species were found to have retained a full set of functional photosynthesis-related genes and housekeeping genes. This study provides important insights into plastid genome degradation along the transition from autotrophy to mycoheterotrophy in a phylogenomic and temporal context.